Der PGR ohne amtliches Mitglied als Impuls für ein neues Rollengefüge - Hofmeister, Lisa; Reis, Oliver (Projektbericht 1: Modelle, Transformationen, Corona-Erfahrungen)

Digitale und digital gestützte Lehre als Verstärker der Verunterrichtlichung von Hochschullehre? - Reis, Oliver (Forschungsimpulse für die Hochschulentwicklung im Kontext hybrider Lehre)

Was leisten modellgeleitete Interventionen für die Kirchenentwicklung? - Reis, Oliver; Kolk, Matthias; Burke, Rebekka; Hackstedt, Carola; Hofmeister, Lisa; Rakowski, Jana (Projektbericht 1: Modelle, Transformationen, Corona-Erfahrungen)

Die Corona-Pandemie als Stresstest der Strukturinterventionen - Burke, Rebekka; Hackstedt, Carola; Hofmeister, Lisa; Reis, Oliver (Projektbericht 1: Modelle, Transformationen, Corona-Erfahrungen)

Opportunities and Possibilities of a Network of Mathematical Learning and Support Centres in Germany - Schürmann, Mirko; Liebendörfer, Michael; Gildehaus, Lara; Schaper, Niclas; Hochmuth, Reinhard; Biehler, Rolf; Lankeit, Elisa; Kuklinski, Christiane; Ruge, Johanna (Sigma newsletter)

Was ist eine gute Skizze? Strategiewissen beim mathematischen Modellieren im Bereich der Geometrie fördern - Schönherr, Johanna; Schukajlow, S.; Blomberg, J. (mathematik lehren)

Does strategic knowledge matter? Effects of strategic knowledge about drawing on students’ modeling competencies in the domain of geometry - Schönherr, Johanna; Schukajlow, S.; Blomberg, J.; Leopold, C. (Mathematical Thinking and Learning)

Do emotions and prior performance facilitate the use of the learner-generated drawing strategy? Effects of enjoyment, anxiety, and intramathematical performance on the use of the drawing strategy and modelling performance - Schönherr, Johanna; Blomberg, J.; Schukajlow, S.; Leopold, C. (Contemporary Educational Psychology)

A fuzzy weighted influence non-linear gauge system with application to advanced technology assessment at NASA - Tavana, Madjid; Mousavi, Hossein; Khalili Nasr, Arash; Mina, Hassan (Expert Systems with Applications)

An integrated data envelopment analysis and life cycle assessment method for performance measurement in green construction management - Tavana, Madjid; Izadikhah, Mohammad; Farzipoor Saen, Reza; Zare, Ramin (Environmental Science and Pollution Research)

An integrated fuzzy sustainable supplier evaluation and selection framework for green supply chains in reverse logistics - Tavana, Madjid; Shaabani, Akram; Santos-Arteaga, Francisco J.; Valaei, Naser (Environmental Science and Pollution Research)

An integrated fuzzy AHP- fuzzy MULTIMOORA model for supply chain risk-benefit assessment and supplier selection - Tavana, Madjid; Shaabani, Akram; Mansouri Mohammadabadi, Soleyman; Varzgani, Nilofar (International Journal of Systems Science: Operations & Logistics)

An epsilon-based data envelopment analysis approach for solving performance measurement problems with interval and ordinal dual-role factors - Ebrahimi, Bohlool; Tavana, Madjid; Kleine, Andreas; Dellnitz, Andreas (OR Spectrum)

An integrated group fuzzy best-worst method and combined compromise solution with Bonferroni functions for supplier selection in reverse supply chains - Tavana, Madjid; Shaabani, Akram; Di Caprio, Debora; Bonyani, Abbas (Cleaner Logistics and Supply Chain)

A location-inventory-routing model for green supply chains with low-carbon emissions under uncertainty - Tavana, Madjid; Tohidi, Hamid; Alimohammadi, Milad; Lesansalmasi, Reza (Environmental Science and Pollution Research)

A novel fuzzy multi-objective circular supplier selection and order allocation model for sustainable closed-loop supply chains - Khalili Nasr, Arash; Tavana, Madjid; Alavi, Behrouz; Mina, Hassan (Journal of Cleaner Production)

An integrated and comprehensive fuzzy multicriteria model for supplier selection in digital supply chains - Tavana, Madjid; Shaabani, Akram; Di Caprio, Debora; Amiri, Maghsoud (Sustainable Operations and Computers)

A note and new extensions on “interval efficiency measures in data envelopment analysis with imprecise data” - Ebrahimi, Bohlool; Tavana, Madjid; Charles, Vincent (Operational Research)

A grey-DEMATEL approach for analyzing factors critical to the implementation of reverse logistics in the pharmaceutical care process - de Campos, Elaine Aparecida Regiani; Tavana, Madjid; ten Caten, Carla Schwengber; Bouzon, Marina; de Paula, Istefani Carísio (Environmental Science and Pollution Research)

An integrated information fusion and grey multi-criteria decision-making framework for sustainable supplier selection - Aslani, Babak; Rabiee, Meysam; Tavana, Madjid (International Journal of Systems Science: Operations & Logistics)

A Systematic Review of Organizational Factors Impacting Cloud-based Technology Adoption Using Technology-Organization-Environment Framework - Al Hadwer, Ali; Tavana, Madjid; Gillis, Dan; Rezania, Davar (Internet of Things)

An inventory-location optimization model for equitable influenza vaccine distribution in developing countries during the COVID-19 pandemic - Rastegar, Mehdi; Tavana, Madjid; Meraj, Afshin; Mina, Hassan (Vaccine)

An Integrated Fuzzy Goal Programming—Theory of Constraints Model for Production Planning and Optimization - Zare, Habib; Kamali Saraji, Mahyar; Tavana, Madjid; Streimikiene, Dalia; Cavallaro, Fausto (Sustainability)

A common weights model for investigating efficiency-based leadership in the russian banking industry - Kazemi, Sajad; Tavana, Madjid; Toloo, Mehdi; Zenkevich, Nikolay A. (RAIRO - Operations Research)

A simulation–optimization model for solving flexible flow shop scheduling problems with rework and transportation - Gheisariha, Elmira; Tavana, Madjid; Jolai, Fariborz; Rabiee, Meysam (Mathematics and Computers in Simulation)

A joint chance-constrained data envelopment analysis model with random output data - Khanjani Shiraz, Rashed; Tavana, Madjid; Fukuyama, Hirofumi (Operational Research)

A Dynamic Decision Support System for Sustainable Supplier Selection in Circular Economy - Alavi, Behrouz; Tavana, Madjid; Mina, Hassan (Sustainable Production and Consumption)

An integrated quality and resilience engineering framework in healthcare with Z-number data envelopment analysis - Tavana, Madjid; Nazari-Shirkouhi, Salman; Farzaneh Kholghabad, Hamidreza (Health Care Management Science)

An integrated fuzzy framework for analyzing barriers to the implementation of continuous improvement in manufacturing - Tavana, Madjid; Shaabani, Akram; Valaei, Naser (International Journal of Quality & Reliability Management)

A fuzzy maturity-based method for lean supply chain management assessment - Soares, Gabriela Pereira; Tortorella, Guilherme; Bouzon, Marina; Tavana, Madjid (International Journal of Lean Six Sigma)

A robust cross-efficiency data envelopment analysis model with undesirable outputs - Tavana, Madjid; Toloo, Mehdi; Aghayi, Nazila; Arabmaldar, Aliasghar (Expert Systems with Applications)

Four research pathways for understanding the role of smart technologies in accounting - Mancini, Daniela; Lombardi, Rosa; Tavana, Madjid (Meditari Accountancy Research)

A new non-radial directional distance model for data envelopment analysis problems with negative and flexible measures - Tavana, Madjid; Izadikhah, Mohammad; Toloo, Mehdi; Roostaee, Razieh (Omega)

The Cologne Picture Naming Test for Language Mapping and Monitoring (CoNaT): An Open Set of 100 Black and White Object Drawings - Weiss Lucas, Carolin; Pieczewski, Julia; Kochs, Sophia; Nettekoven, Charlotte; Grefkes, Christian; Goldbrunner, Roland; Jonas, Kristina (Frontiers in Neurology)
Language assessment using a picture naming task crucially relies on the interpretation of the given verbal response by the rater. To avoid misinterpretations, a language-specific and linguistically controlled set of unambiguous, clearly identifiable and common object–word pairs is mandatory. We, here, set out to provide an open-source set of black and white object drawings, particularly suited for language mapping and monitoring, e.g., during awake brain tumour surgery or transcranial magnetic stimulation, in German language. A refined set of 100 black and white drawings was tested in two consecutive runs of randomised picture order and was analysed in respect of correct, prompt, and reliable object recognition and naming in a series of 132 healthy subjects between 18 and 84 years (median 25 years, 64% females) and a clinical pilot cohort of 10 brain tumour patients (median age 47 years, 80% males). The influence of important word- and subject-related factors on task performance and reliability was investigated. Overall, across both healthy subjects and patients, excellent correct object naming rates (97 vs. 96%) as well as high reliability coefficients (Goodman–Kruskal's gamma = 0.95 vs. 0.86) were found. However, the analysis of variance revealed a significant, overall negative effect of low word frequency ( p < 0.05) and high age ( p < 0.0001) on task performance whereas the effect of a low educational level was only evident for the subgroup of 72 or more years of age ( p < 0.05). Moreover, a small learning effect was observed across the two runs of the test ( p < 0.001). In summary, this study provides an overall robust and reliable picture naming tool, optimised for the clinical use to map and monitor language functions in patients. However, individual familiarisation before the clinical use remains advisable, especially for subjects that are comparatively prone to spontaneous picture naming errors such as older subjects of low educational level and patients with clinically apparent word finding difficulties.

Improving the efficacy and reliability of rTMS language mapping by increasing the stimulation frequency - Nettekoven, Charlotte; Pieczewski, Julia; Neuschmelting, Volker; Jonas, Kristina; Goldbrunner, Roland; Grefkes, Christian; Weiss Lucas, Carolin (Human Brain Mapping)
Abstract Repetitive TMS (rTMS) with a frequency of 5–10 Hz is widely used for language mapping. However, it may be accompanied by discomfort and is limited in the number and reliability of evoked language errors. We, here, systematically tested the influence of different stimulation frequencies (i.e., 10, 30, and 50 Hz) on tolerability, number, reliability, and cortical distribution of language errors aiming at improved language mapping. 15 right‐handed, healthy subjects (m = 8, median age: 29 yrs) were investigated in two sessions, separated by 2–5 days. In each session, 10, 30, and 50 Hz rTMS were applied over the left hemisphere in a randomized order during a picture naming task. Overall, 30 Hz rTMS evoked significantly more errors (20 ± 12%) compared to 50 Hz (12 ± 8%; p <.01), whereas error rates were comparable between 30/50 and 10 Hz (18 ± 11%). Across all conditions, a significantly higher error rate was found in Session 1 (19 ± 13%) compared to Session 2 (13 ± 7%, p <.05). The error rate was poorly reliable between sessions for 10 (intraclass correlation coefficient, ICC = .315) and 30 Hz (ICC = .427), whereas 50 Hz showed a moderate reliability (ICC = .597). Spatial reliability of language errors was low to moderate with a tendency toward increased reliability for higher frequencies, for example, within frontal regions. Compared to 10 Hz, both, 30 and 50 Hz were rated as less painful. Taken together, our data favor the use of rTMS‐protocols employing higher frequencies for evoking language errors reliably and with reduced discomfort, depending on the region of interest.

Confinement Effects for Efficient Macrocyclization Reactions with Supported Cationic Molybdenum Imido Alkylidene N-Heterocyclic Carbene Complexes - Ziegler, Felix; Kraus, Hamzeh; Benedikter, Mathis J.; Wang, Dongren; Bruckner, Johanna R.; Nowakowski, Michał; Weißer, Kilian; Solodenko, Helena; Schmitz, Guido; Bauer, Matthias; Hansen, Niels; Buchmeiser, Michael R. (ACS Catalysis)
For entropic reasons, the synthesis of macrocycles via olefin ring-closing metathesis (RCM) is impeded by competing acyclic diene metathesis (ADMET) oligomerization. With cationic molybdenum imido alkylidene N-heterocyclic carbene (NHC) complexes confined in tailored ordered mesoporous silica, RCM can be run with macrocyclization selectivities up to 98% and high substrate concentrations up to 0.1 M. Molecular dynamics simulations show that the high conversions are a direct result of the proximity between the surface-bound catalyst, proven by extended X-ray absorption spectroscopy, and the surface-located substrates. Back-diffusion of the macrocycles decreases with decreasing pore diameter of the silica and is responsible for the high macrocyclization efficiency. Also, Z-selectivity increases with decreasing pore diameter and increasing Tolman electronic parameter of the NHC. Running reactions at different concentrations allows for identifying the optimum substrate concentration for each material and substrate combination.
Keywords: Catalysis; General Chemistry

Rh(I)/(III)‐N‐Heterocyclic Carbene Complexes: Effect of Steric Confinement Upon Immobilization on Regio‐ and Stereoselectivity in the Hydrosilylation of Alkynes - Panyam, Pradeep K. R.; Atwi, Boshra; Ziegler, Felix; Frey, Wolfgang; Nowakowski, Michał; Bauer, Matthias; Buchmeiser, Michael R. (Chemistry – A European Journal)
Rh(I) NHC and Rh(III) Cp* NHC complexes (Cp*=pentamethylcyclopentadienyl, NHC=N-heterocyclic carbene=pyrid-2-ylimidazol-2-ylidene (Py−Im), thiophen-2-ylimidazol-2-ylidene) are presented. Selected catalysts were selectively immobilized inside the mesopores of SBA-15 with average pore diameters of 5.0 and 6.2 nm. Together with their homogenous progenitors, the immobilized catalysts were used in the hydrosilylation of terminal alkynes. For aromatic alkynes, both the neutral and cationic Rh(I) complexes showed excellent reactivity with exclusive formation of the β(E)-isomer. For aliphatic alkynes, however, selectivity of the Rh(I) complexes was low. By contrast, the neutral and cationic Rh(III) Cp* NHC complexes proved to be highly regio- and stereoselective catalysts, allowing for the formation of the thermodynamically less stable β-(Z)-vinylsilane isomers at room temperature. Notably, the SBA-15 immobilized Rh(I) catalysts, in which the pore walls provide an additional confinement, showed excellent β-(Z)-selectivity in the hydrosilylation of aliphatic alkynes, too. Also, in the case of 4-aminophenylacetylene, selective formation of the β(Z)-isomer was observed with a neutral SBA-15 supported Rh(III) Cp* NHC complex but not with its homogenous counterpart. These are the first examples of high β(Z)-selectivity in the hydrosilylation of alkynes by confinement generated upon immobilization inside mesoporous silica.
Keywords: General Chemistry; Catalysis; Organic Chemistry

Immobilized Platinum Hydride Species as Catalysts for Olefin Isomerizations and Enyne Cycloisomerizations - Maier, Sarah; Cronin, Steve P.; Vu Dinh, Manh-Anh; Li, Zheng; Dyballa, Michael; Nowakowski, Michał; Bauer, Matthias; Estes, Deven P. (Organometallics)
Platinum hydride species catalyze a number of interesting organic reactions. However, their reactions typically involve the use of high loadings of noble metal and are difficult to recycle, making them somewhat unsustainable. We have synthesized surface-immobilized Pt–H species via oxidative addition of surface OH groups to Pt(PtBu3)2 (1), a rarely used immobilization technique in surface organometallic chemistry. The hydride species thus made were characterized by infrared, magic-angle spinning nuclear magnetic resonance, and X-ray absorption spectroscopies and catalyzed both olefin isomerization and cycloisomerization of a 1,6 enyne (5) with a high selectivity and low Pt loading.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry

Fundamental Characterization, Photophysics and Photocatalysis of a Base Metal Iron(II)‐Cobalt(III) Dyad - Huber-Gedert, Marina; Nowakowski, Michał; Kertmen, Ahmet; Burkhardt, Lukas; Lindner, Natalia; Schoch, Roland; Herbst‐Irmer, Regine; Neuba, Adam; Schmitz, Lennart; Choi, Tae‐Kyu; Kubicki, Jacek; Gawelda, Wojciech; et al. (Chemistry – A European Journal)
Keywords: Photocatalytic Hydrogen Production; Catalysis; Inorganic Chemistry

Work-related practices of local managers of live music events in Ostwestfalen-Lippe (OWL) and their impact on cultural participation - Flath, Beate; Momen Pour Tafreshi, Maryam (Arts and the Market)
Purpose The purpose of this article is to illuminate the relations of work-related practices of local managers of live music events in Ostwestfalen-Lippe (OWL) and barriers and needs of vulnerable customers (VC) in order to explore possibilities to increase cultural participation of VC. Design/methodology/approach This article explores work-related practices of managers of live music events in OWL and asks if and to what extent these practices have an influence on the cultural participation of “vulnerable customers” (VC). It combines the findings of two studies: a) an explorative investigation on the work-related self-conceptions of managers of live music events in OWL (Study 1), and b) a sub-project on cultural participation of VC, which is part of the research project “kulturPreis. Increasing cultural participation through innovative and economically sustainable pricing concepts”, funded by the German Federal Ministry of Education and Research (Study 2). Findings It can be stated that there is an imbalance of knowledge: while VC tend to have a clear understanding of which barriers are the responsibility of managers of live music events, managers tend to lack knowledge regarding the needs of VC, and regarding the interrelationships between financial and social barriers facing them. Whether this knowledge and understanding can be developed in the future depends on the possibilities of exchanges between managers of live music events, cultural institutions, welfare organisations, political institutions and not least VC. Originality/value Based on these studies, this article combines different approaches by linking work-related practices of managers of live music events with cultural participation of VC.

Digitale Stille. Über die Bedeutung von Universitäten und Wissenschaft in der Covid-19-Pandemie - Flath, Beate (Das HEFT. Das Paderborner Veranstaltungs- und Kulturmagazin)

Data-Based Co-Creation and Participation: Reflections on an Ambivalent Relation by the Example of Music Apps - Flath, Beate (Pop – Power – Positions. Globale Beziehungen und populäre Musik (~Vibes – The IASPM D-A-CH Series 1)

Das Besondere und das Allgemeine in musikdidaktischen Kontexten. - Klingmann, Heinrich (Musikalische Bildung. Didaktik - Lehrerinnen- und Lehrerbildung - Theorie. Festschrift für Werner Jank.)

Doing Popkultur. - Klingmann, Heinrich; Ahlers, Michael (Musik-Didaktik. Praxishandbuch für die Sekundarstufe 1 und 2)

Textsortengeschichte - Markewitz, Friedrich (WSK Band 6 (Wörterbücher zur Sprach- und Kommunikationswissenschaft): Text- und Diskurslinguistik)

Das „geheime Europa“. Hugo von Hofmannsthals späte Parallelaktion zu Stefan Georges „geheimem Deutschland“ (1919–1923) - Heise, Tillmann („Sehnsucht nach dem Leben“. Tradition und Innovation im Werk Hugo von Hofmannsthals)

Das ‚Erfundene Gespräch‘ als transatlantischer Dialog. Gattungsvariationen und Gedankenexperimente in Hofmannsthals Gesprächsfragment "Brief ans Dial" (1925) - Heise, Tillmann (Hofmannsthal-Jahrbuch)

Verfreundete Europäer im Kampf mit der Moderne - Heise, Tillmann; Beßlich, Barbara (Ruperto Carola Forschungsmagazin)

A mathematical programming approach for equitable COVID-19 vaccine distribution in developing countries - Tavana, Madjid; Govindan, Kannan; Nasr, Arash Khalili; Heidary, Mohammad Saeed; Mina, Hassan (Annals of Operations Research)

Kriterien der Sanktionierung einer Verletzung der Bonitätsprüfungspflicht - Bartlitz, David (Neue Juristische Wochenschrift (NJW))